인공위성의 고효율 열제어 구현을 위한 액체금속형 가변 전도율 방열판에 관한 연구 - 박귀중(Gwi-Jung Park); 고지성(Ji-Seong Go); 오현웅(Hyun-Ung Oh) (항공우주시스템공학회지, 2019)
The observation satellites which uses high heat-dissipating equipment such as synthetic aperture radar (SAR) satellites require a radiator to transmit heat from the equipment into outer space. However, during cold conditions it requires a heater to maintain the temperature of equipment within the allowable minimum limit when it is not in operation. In this study, we proposed a variable conductivity radiator that changes its thermal conductivity value through movement of the liquid metal between two reservoirs based on the temperature condition. This reduces the power consumption of the heater by limiting heat transfer path to the radiator in cold condition, while effectively transferring heat to the radiator during hot condition. The feasibility of the proposed radiator was validated through comparison of the thermal control performance with the conventional fixed conductivity radiator via a thermal analysis. SAR(Synthetic Aperture Radar) 관측위성과 같이 고 발열 임무장비가 다수 적용되는 경우 전장품의 발열을 효과적으로 우주공간으로 방출하기 위한 방열판의 적용이 요구된다. 그러나 위성의 식 구간에서 임무장비의 비작동 시, 방열판을 통해 지속적인 방열이 이루어짐에 따라 장비의 최소허용 온도유지를 위한 히터 적용이 불가피하게 된다. 본 연구에서는 기존 방열판에 비해 보다 효율적인 열제어를 위하여 높은 전도율의 액체금속을 이용한 우주용 가변 전도율 방열판을 제안하였다. 제안된 방열판은 탑재장비의 온도조건에 따라 두 개의 저장소 사이에서 기계식 펌프로 액체금속을 이동함으로서 열전도 특성을 가변하는 원리이다. 따라서 저온 조건에서는 방열판으로의 열전도를 차단하여 임무장비에 대한 히터 전력소모를 최소화하고, 반대로 고온 조건에서는 기존 방열판과 같이 효과적인 방열이 가능하도록 한다. 본 연구에서는 제안한 가변 전도율 방열판의 실현 가능성 입증을 위한 열해석을 실시하여 기존의 전도율이 고정된 방열판과 열적 성능을 비교 분석하였다.